Liquid-nano-liquid interface–oriented anisotropic encapsulation - Yating Zhan; Xirui Huang; Minchao Liu; Runfeng Lin; Hongyue Yu; Yufang Kou; Enyun Xing; Ahmed A. Elzatahry; Mohamed F. Mady; Dongyuan Zhao; Tiancong Zhao; Xiaomin Li (Proceedings of the National Academy of Sciences, 2025)
Emulsion interface engineering has been widely employed for the synthesis of nanomaterials with various morphologies. However, the instability of the liquid–liquid interface and uncertain interfacial interactions impose significant limitations on controllable fabrications. Here, we developed a liquid-nano-liquid interface–oriented anisotropic encapsulation strategy for fabricating asymmetric nanohybrids. Specifically, functional nanoparticles such as magnetic nanoparticles, lanthanide fluorescent nanoparticles, and Au nanorods were anisotropically encapsulated by mesoporous polydopamine (mPDA). In this emulsion system, the wetting behavior of functional nanoparticles at the water/oil interface could be manipulated by the stabilizer of the emulsion (surfactant), leading to the anisotropic assembly of mPDA shell and resulting in various nanostructures, including core–shell, yolk–shell with small opening, ball-in-bowl, and multipetal structures. Due to their structural asymmetry, inherent magnetic properties, and photothermal properties, the ball-in-bowl structured Fe 3 O 4 @SiO 2 &mPDA nanohybrids, serving as proof of concept for nanomotors, demonstrated effective penetration of bacterial biofilm and promotion of infected wound healing. Overall, our approach offers a different perspective for designing morphologically controllable asymmetric structures based on liquid-nano-liquid interface in microemulsion systems that hold great potential for establishing innovative functional nanomaterials.